Brittle crack propagation acceleration in a single crystal of a 3% silicon-Fe alloy - Tomoya Kawbata; Noritaka Nakamura; Shuji Aihara (Fracture and Structural Integrity)
Brittle fracture in carbon steel has a serious impact on the safety of steel structures. Thus, technology that arrests crack propagation is the final line of protection for such structures. It is such an important issue that conditions that can reliably stop crack propagation should be thoroughly clarified. Due to the social importance of the problem, many experimental and theoretical studies have been conducted from both the mechanical and microstructural viewpoints.